2002
DOI: 10.1046/j.1365-2591.2002.00473.x
|View full text |Cite
|
Sign up to set email alerts
|

Guided bone regeneration (GBR) using membranes and calcium sulphate after apicectomy: a comparative histomorphometrical study

Abstract: The data suggests that e-PTFE membrane is more effective compared to resorbable membranes and controls for bone regeneration after apicectomy, and that calcium sulphate could be substituted for e-PTFE membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 26 publications
3
52
0
1
Order By: Relevance
“…Yoshikawa et al, 4 in an experimental study in dogs with the use of e-PTFE membranes and CaS after apicectomy, found that bone regeneration with the use of CaS was similar to that obtained using e-PTFE and superior to controls. Pecora et al, 3 in a study using CaS in the surgical treatment of a through and through periradicular lesion, found that the addition of calcium sulfate to conventional surgical treatment of this type of endodontic lesions may contribute to an improvement of the clinical outcome.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Yoshikawa et al, 4 in an experimental study in dogs with the use of e-PTFE membranes and CaS after apicectomy, found that bone regeneration with the use of CaS was similar to that obtained using e-PTFE and superior to controls. Pecora et al, 3 in a study using CaS in the surgical treatment of a through and through periradicular lesion, found that the addition of calcium sulfate to conventional surgical treatment of this type of endodontic lesions may contribute to an improvement of the clinical outcome.…”
Section: Discussionmentioning
confidence: 91%
“…[5][6][7][8][9][10][11][12] Calcium sulfate has been successfully used to treat periodontal disease, endodontic lesions, alveolar bone loss, and maxillary sinus augmentation. 3,4,[13][14][15][16][17] Calcium sulfate may act as a binder, facilitating healing and preventing loss of the grafting material; moreover, it is tissue compatible, and does not interfere with the healing process. 18 Calcium sulfate has also been used with other materials, such as autogenous bone, 2 DFDBA, 18 polymers, or HA; 19 in these cases there was a favorable effect on the potential for osteogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, the defect area must first be reconstructed before artificial tooth root implantation. To this end, guided bone regeneration (GBR) procedures have been noted as a reliable periodontal regeneration and alveolar augmentation therapy, and have registered high success rates in recent years [4]. Currently, there are two material systems for GBR procedures, namely degradable and non-degradable membrane materials [5].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In some cases, such as through-and-through osseous defects and in combined endodontic-periodontal lesions, there is large bone destruction which hinders apical healing by periodontal tissue regeneration. 3 Osseous defects may be repaired in two ways: healing by periodontal tissue regeneration or by fibrous scar tissue. Natural regeneration of large bone defects is usually incomplete and occurs by fibrous tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, if a non-resorbable membrane is used, a second surgery is required to remove the membrane. 3 Lyophilized anorganic bovine bone is among the different types of material used for grafting. It is a xenograft obtained through deproteinization at high temperatures.…”
Section: Introductionmentioning
confidence: 99%